2021
DOI: 10.1016/j.stemcr.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid precursors and progenitors suppress adaptive immunity and get invaded by SARS-CoV-2

Abstract: SARS-CoV-2 infection is associated with lower blood oxygen levels, even in patients without hypoxia requiring hospitalization. This discordance illustrates the need for a more unifying explanation as to whether SARS-CoV-2 directly or indirectly affects erythropoiesis. Here, we show significantly enriched CD71 + erythroid precursors/progenitors in the blood circulation of COVID-19 patients. We found that these cells have distinctive immunosuppressive properties. In agreement, we observed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 72 publications
(109 reference statements)
6
94
1
4
Order By: Relevance
“…In a previous study, 200 μM HOCl was found to react with and destroy the heme of hemoglobin in red blood cells [ 12 ]. This is consistent with recent work by Elahi et al, in which the harmful effect of COVID-19 on red blood cells is demonstrated [ 46 ].…”
Section: Hocl-associated Hemoprotein Heme Destructionsupporting
confidence: 94%
“…In a previous study, 200 μM HOCl was found to react with and destroy the heme of hemoglobin in red blood cells [ 12 ]. This is consistent with recent work by Elahi et al, in which the harmful effect of COVID-19 on red blood cells is demonstrated [ 46 ].…”
Section: Hocl-associated Hemoprotein Heme Destructionsupporting
confidence: 94%
“…The virus can infect erythroid precursor cells. This, in turn, leads to a greater production of immature red blood cells, followed by their massive release into the bloodstream and a corresponding drop in hemoglobin levels [ 24 ].…”
Section: Factors Determining the Disruption Of Gas Exchange In Covid-19mentioning
confidence: 99%
“…Extensive studies revealed its neglected immunomodulatory properties under other different physiological and pathological conditions, too. CEC is heterogeneous, which could be induced by tumor, injury (8), pregnancy (9), systemic inflammation (10), HIV infection (11), and even COVID-19 (12,13). All phenotypes have immunomodulatory functions.…”
Section: Introductionmentioning
confidence: 99%